Undergraduate teaching in geriatric medicine using computer-aided learning improves student performance in examinations. - Daunt, Laura A.; Umeonusulu, Patience I.; Gladman, John R. F.; Blundell, Adrian G.; Conroy, Simon P.; Gordon, Adam L. (Age & Ageing, 2013)
Background: computer-aided learning (CAL) is increasingly used to deliver teaching, but few studies have evaluated its impact on learning within geriatric medicine. We developed and implemented CAL packages on falls and continence, and evaluated their effect on student performance in two medical schools.Methods: traditional ward based and didactic teaching was replaced by blended learning (CAL package combined with traditional teaching methods). Examination scores were compared for cohorts of medical students receiving traditional learning and those receiving blended learning. Control questions were included to provide data on cohort differences.Results: in both medical schools, there was a trend towards improved scores following blended learning, with a smaller number of students achieving low scores (P < 0.01). Feedback from students about the CAL packages was positive.Discussion: blended learning was associated with improvement in student examination performance, regardless of the setting or the methods adopted, and without increasing teaching time. Our findings support the use of CAL in teaching geriatric medicine, and this method has been adopted for teaching other topics in the undergraduate curriculum.